Single-vehicle and Multi-vehicle Accidents Involving Motorcycles in a Small City in China: Characteristics and Injury Patterns - Lili Xiong; Liping Li (AIMS Press, 2015)
Introduction: There is a gap that involves examining differences between patients in single-vehicle (SV) versus multi-vehicle (MV) accidents involving motorcycles in Shantou, China, regarding the injury patterns and mortality the patients sustained. This study aims to address this gap and provide a basis and reference for motorcycle injury prevention. Method: Medical record data was collected between October 2002 and June 2012 on all motorcycle injury patients admitted to a hospital in the city of Shantou of the east Guangdong province in China. Comparative analysis was conducted between patients in SV accidents and patients in MV accidents regarding demographic and clinic characteristics, mortality, and injury patterns. Results: Approximately 48% (n = 1977) of patients were involved in SV accidents and 52% (n = 2119) were involved in MV accidents. The average age was 34 years. Collision of a motorcycle with a heavy vehicle/bus (4%) was associated with a 34 times greater risk of death (RR: 34.32|95% CI: 17.43-67.57). Compared to patients involved in MV accidents, those involved in SV accidents were more likely to sustain a skull fracture (RR: 1.47|95% CI: 1.22-1.77), an open head wound (RR: 1.46|95% CI: 1.23-1.74), an intracranial injury (RR: 1.39|95% CI: 1.26-1.53), a superficial head injury (RR: 1.37|95% CI: 1.01-1.86), an injury to an organ (RR: 2.01|95% CI: 1.24-3.26), and a crushing injury (RR: 1.98|95% CI: 1.06-3.70) to the thorax or abdomen. However, they were less likely to sustain a spinal fracture (RR: 0.58|95% CI: 0.39-0.85), a pelvic fracture (RR: 0.22|95% CI: 0.11-0.46), an upper extremity fracture (RR: 0.75|95% CI: 0.59-0.96), or injuries to their lower extremities, except for a dislocation, sprain, or injury to a joint or ligament (RR: 0.82|95% CI: 0.49-1.36). Conclusion: The relative risk of death is higher for patients involved in multi-vehicle accidents than patients in single-vehicle accidents, especially when a collision involves mass vehicle(s). Injury to the head dominated motorcycle injuries. Single-vehicle accidents have a higher correlation with head injury or internal injuries to the thorax or abdomen. Multi-vehicle accidents are more correlated with extremity injuries, especially to the lower extremities or external trauma to the thorax or abdomen.